1998
DOI: 10.1038/sj.bmt.1701464
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet transfusion requirement is associated with multiple organ dysfunctions in patients undergoing hematopoietic stem cell transplantation

Abstract: Summary:Organ dysfunction following hematopoietic stem cell transplantation (HSCT) may be a manifestation of a systemic inflammatory response. We speculate that part of the platelet transfusion requirement in HSCT patients results from this systemic inflammatory response, and increased transfusion requirement would be associated with, or precede, organ dysfunction. We studied 199 adults undergoing autologous (n = 173) or allogeneic (n = 26) HSCT. Patients with CNS (P = 0.008) or pulmonary (P = 0.002) dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…6,12,13,15 As previously stated, subtle changes in pulmonary, CNS, or liver function identifies a group of patients with high risk for death. Patients with pulmonary dysfunction or CNS changes had a 4.9-and 18-fold increased risk of dying after stem cell transplantation, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…6,12,13,15 As previously stated, subtle changes in pulmonary, CNS, or liver function identifies a group of patients with high risk for death. Patients with pulmonary dysfunction or CNS changes had a 4.9-and 18-fold increased risk of dying after stem cell transplantation, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Patients developing OD may be identified by a decline in pulmonary, central nervous system, or hepatic function and often have corresponding laboratory abnormalities including a drop in antithrombin III and protein C concentrations and an increased platelet utilization. 6,12 Regardless of which of these abnormalities is the first to be recognized, affected patients are at risk of progressing to MODS and death. 1,13 The importance of developing these clinical abnormalities is difficult to overestimate, with one study reporting no mortality in patients without signs of early OD compared to 46% mortality in patients who showed signs of early OD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Platelet engraftment can be impeded by the occurrence post transplant of complications of veno-occlusive disease (VOD) and GVHD in allogeneic HSCT. 2 Indeed, in the presence of GVHD, recovery of platelet count is a slow and gradual process, with 50% of patients remaining thrombocytopenic at day 50. 3 The incidence of major bleeding owing to prolonged thrombocytopenia ranged between 14 and 17% in one series evaluating platelet transfusion threshold in HSCT recipients.…”
Section: Bleeding; Thrombocytopeniamentioning
confidence: 99%
“…7 Increased platelet transfusion requirement is usually associated with VOD. Gordon et al 8 retrospectively reviewed platelet requirements in 199 patients who underwent transplant at the University of Nebraska. They found that patients with dysfunction of a single organ (VOD, pulmonary or CNS) received more platelet transfusions per week compared to patients without organ dysfunction.…”
mentioning
confidence: 99%